Bilateral Transfer for Learning to Control Timing but Not for Learning to Control Fine Force. Issue 2 (April 2014) - Yao, Wan X.; Cordova, Alberto; Huang, Yufei; Wang, Yan; Lu, Xing
This study examined the characteristics of bilateral transfer of learning to control timing and fine force from a dominant limb to a nondominant limb. 20 right-handed college students (12 women, 8 men; M age = 21.5 yr., SD = 2.3) learned a sequential task consisting of timing and force control. Each participant completed a pre-test of the task with both hands and then performed 100 practice trials with the dominant hand. A post-test was conducted 1 hr. later. The results showed that after training, participants learned to control the timing and force. Nevertheless, only the time-control learning was transferred to the untrained hand, whereas the force-control learning did not transfer to the untrained hand.